Navigating e-learning participation: A look at Sabah school students' post- pandemic experiences - Asmaa Abdulhameed Mohammad Al-saqqaf; Ke Hu (Penerbit Universiti Sultan Zainal Abidin, 2025)
The aftermath of the COVID-19 virus has begun to sweep across Malaysia again at the end of 2023, with uncertainties whether educational institutions should reopen online teaching. It is important to note that during and in the post-era of COVID-19 pandemic, the level of participation among primary and secondary school students in Sabah, Malaysia was at the centre of the educators’ discussion, yet it did not receive adequate attention by researchers. Despite its advantages, e-learning proved to be challenging to engage school students which inevitably affected students’ learning productivity. This study aimed to investigate the level of participation in E-learning among school students in Kota Kinabalu during COVID-19 and identify whether there was any difference in the level of e-learning participation based on demographic variables. A Google Form survey was distributed to 247 students from various schools in Kota Kinabalu, selected through simple random sampling. The data was analyzed using SPSS 29.0. The descriptive findings revealed a moderate level of participation with e-learning among the school students, with an average score of 3.37. Contrary to expectations, ANOVA results indicated that student participation in e-learning remained consistent across age groups, with both primary and secondary students demonstrating similar levels of participation, suggesting that both male and female students adapted equally well to e-learning. While the immediate impact of COVID-19 on education is lessening, its long-term effects will require sustained focus and effort to mitigate. Enhancing student participation in e-learning is crucial for improving the educational process and ensuring meaningful learning during unexpected crises.